Ejercicios de Core en pacientes adultos con lumbalgia - Erika Jazmin, Bustillos Oñate (2021)
This research demonstrates Core exercises' benefits as a physiotherapeutic treatment in adult patients with low back pain. Low back pain is discomfort, limitation in the lumbar area that extends between the lower edge of the last ribs and the lower fold of the gluteus area without irradiation to the lower limbs; triggers are heavy physical work, forced posture, weakening of the abdominal and lumbar muscles. Low back pain is classified according to pain: Acute low back pain limits daily activity for less than three months. Patients generally improve in the first six weeks, even without having an etiological diagnosis. Chronic low back pain extends beyond three months, for which a Core exercise program is used that provides stability, balance, and coordination to the body for any movement, which encompasses the entire abdominal region and lower back. It is made up of the oblique ones, rectal abdominal, pelvic floor, diaphragm, multifidus, and the most important muscle of all: the transverse abdominal muscle. The present research was developed in the bibliographic review modality; it consists of proven scientific material to demonstrate that Core's exercise-based physiotherapeutic program presents favorable results in adult patients with low back pain. To verify this hypothesis, 65 scientific articles were used that try to expose the subject to be discussed. However, they do not comply with the PEDro scale assessment, of which 35 meet the criteria for the development of this research, 25 are intervention articles that demonstrate the effectiveness of the application of Core exercises to adult patients with low back pain. At the same time, the remaining 10 show physiotherapeutic approaches for low back pain. The articles were extracted from the databases of PubMed, Scielo, Elsevier, Lilacs, Google Scholar, PEDro, Scopus, and ProQuest.